Critical Theory, Democracy, and the Challenge of Neoliberalism - Caterino, Brian; Hansen, Phillip, 1949-; Project Muse. (London : University of Toronto Press, 2019)
"With a few exceptions, critical theorists have been late to provide a comprehensive diagnosis of neoliberalism comparable in scope to their extensive analyses of advanced welfare state capitalism. Instead, the main lines of critical theory have focused on questions of international justice which, while no doubt significant, restrict the scope of critical theory by deemphasizing linkages to larger political and economic conditions. Providing a critique of the Frankfurt School, Brian Caterino and Phillip Hansen move beyond its foundations, and call for a rethinking of the bases of critical theory as a practical, freedom-creating project. Outlining a resurgence of neoliberalism, the authors encourage a fresh, nuanced analysis that elucidates its political and economic structures and demonstrates the threats to freedom and democracy that neoliberalism poses; the reformulation of a radical democratic alternative to neoliberalism, one that critically addresses its limitations while promoting an enhancement of communicative and social freedom."--
Introduction -- Macpherson, Habermas, and the demands of democratic theory -- Reason, truth, and power: the challenges of contepmorary critical theory -- Critical theroy and neoliberalism -- Towards a critical theory of democracy: deliberation, self-interest, and solidarity -- Towards a critical theory of democracy: the Frankfurt School and democratic theory -- Towards a critical theory of democracy: participatory democracy and social freedom -- Conclusion: critical theory and radical reform.
Description based on print version record.
Keywords: POLITICAL SCIENCE / General; Neoliberalism; Liberty -- Philosophy; Frankfurt school of sociology; Democracy -- Philosophy; Critical theory; POLITICAL SCIENCE -- General; critical theories (dialectical critiques); Theorie critique; Neo-liberalisme.; Liberte -- Philosophie; École de Francfort (Sociologie); Democratie -- Philosophie; Neoliberalism; Liberty -- Philosophy; Frankfurt school of sociology; Democracy -- Philosophy; Critical theory; Electronic books